Medial Femoral Trochlea Graft for Scaphoid Waist Nonunion: A Case Report and Review of the Literature - Crepaldi, Bruno E.; Keating, Cameron; Ek, Eugene T.; Tham, Stephen K. Y. (Journal of Wrist Surgery, 2020)
The medial femoral trochlea (MFT) of the knee is a donor site for convex osteochondral vascularized bone that has been used for the salvage of fractures of the proximal pole of the scaphoid. Chronic nonunited fractures of the scaphoid may lead to a sequence of degenerative change often referred to as scaphoid nonunion advance collapse. The vascularized MFT osteochondral graft has been reported as a salvage procedure for fractures of the proximal pole of the scaphoid, in situations where fixation is not an option. In this “Special review,” we describe the technique of free vascularized MFT graft in a case in which the nonunited scaphoid fracture was associated with segmental loss of the articular surface of the scaphoid waist. Given the likely progression of arthritis, if left untreated, we elected to treat this by replacing the lost articular surface using a vascularized intercalary osteochondral MFT graft between the nonunited scaphoid segments.
Keywords: scaphoid; fracture; carpal; medial femoral trochlear; non-union